2012
DOI: 10.1073/pnas.1209721109
|View full text |Cite
|
Sign up to set email alerts
|

Targeting collagen strands by photo-triggered triple-helix hybridization

Abstract: Collagen remodeling is an integral part of tissue development, maintenance, and regeneration, but excessive remodeling is associated with various pathologic conditions. The ability to target collagens undergoing remodeling could lead to new diagnostics and therapeutics as well as applications in regenerative medicine; however, such collagens are often degraded and denatured, making them difficult to target with conventional approaches. Here, we present caged collagen mimetic peptides (CMPs) that can be phototr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
246
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(256 citation statements)
references
References 43 publications
(44 reference statements)
10
246
0
Order By: Relevance
“…When staining tissue sections with fluorescently labeled CMPs, we found it beneficial to incubate the samples in the UV-activated peptide solutions at 4 °C, because the triple helical hybridization is facilitated at lower temperature 1,20 . It was also found that immersing the slides in fresh PBS buffer in a staining jar is the most effective way to wash off unbound CMPs, which works much better than merely pipetting washing buffers over the samples.…”
Section: Representative Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When staining tissue sections with fluorescently labeled CMPs, we found it beneficial to incubate the samples in the UV-activated peptide solutions at 4 °C, because the triple helical hybridization is facilitated at lower temperature 1,20 . It was also found that immersing the slides in fresh PBS buffer in a staining jar is the most effective way to wash off unbound CMPs, which works much better than merely pipetting washing buffers over the samples.…”
Section: Representative Resultsmentioning
confidence: 99%
“…This protocol focuses on the imaging application of CMPs as related to collagen remodeling. Methods for CMP synthesis can be found in previous reports 1,7,[9][10][11][12][13][14][15] . In this video report, imaging skeletal tissues in normal mice and tissue sections of mouse cornea were chosen for demonstration purpose; however the methods presented here can be readily applied to many pathologies and biological models involving collagen remodeling (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collagen mimetic peptides are photo-triggered and have a tendency to form a triple helix with the denatured collagen. The CMPs were tagged with Near Infrared Fluorophore (NIRF) (IR-Ahx-(GPO)9 ) and fluorescence revealed the accumulation of the triple helical structure in the tumor tissue [77].…”
Section: Extracellular Matrixmentioning
confidence: 99%